Pengaruh Firm Size Terhadap Nilai Perusahaan dengan Profitabilitas dan Liabilitas sebagai Variabel Mediasi pada Sektor Finance yang Terdaftar di BEI Tahun 2016-2020 - Ria Khoirunnisa' (Jurnal Ilmu Manajemen, 2022)
This study aims to determine the effect of firm size on firm value with profitability and liability as mediating variables. This research focuses on the finance sector listed on the Indonesia Stock Exchange (IDX) for 2016-2020. The finance sector experienced a relatively stable movement on the IDX compared to other industries, but the Jakarta Composite Index (JCI) experienced a decline. The type of research used is research with a quantitative approach and is included in causal analysis. The population in this study were 94 companies. This research used the purposive sampling technique, and 10 companies were taken as samples. The data was analysed using Path Analysis with SmartPLS 3.0. This study indicates that firm size affects liabilities because large firms quickly obtain credit. Firm size does not affect firm value because the number of company assets does not increase profits. Firm size also did not affect profitability because the high costs of managing the company will reduce profitability. Profitability affects firm value because high profitability can increase investor interest. Liabilities affect the company's worth because the more outstanding debt will increase the risk to reduce the value of the company. Profitability and liability cannot be mediating variables between firm size and firm weight because, partially, the firm size variable is not significantly affected in this study.